Minding the Gap: Marxian Reflections on the Transition from Capitalism to Postcapitalism - Bryant William Sculos (tripleC: Communication, Capitalism & Critique)
Building on contemporary debates over the past several decades in Marxist and post-Marxist theory regarding the relationship between capitalism and postcapitalism, this essay will explore the enduring relevance of Marx’s treatment of this issue in some of his most significant, though increasingly less contemporarily engaged with texts (as Capital [Vols. 1-3] and the Grundrisse take pride of place). Here, I look toward the middle and early period of Marx’s oeuvre to pull out the most important statements and insights regarding the relationship between capitalism and postcapitalism, focusing on The German Ideology, The 18th Brumaire of Louis Bonaparte, Economic and Philosophic Manuscripts of 1844, and The Communist Manifesto in order to offer reflections on how Marx’s work, 200 years since his birth, offer the contemporary and future left guidance on “minding the gap” between capitalism and postcapitalism as we live, work, and struggle still deeply ensconced within the confines of the decadent capitalist mode of production. Combing close-reading of key relevant texts in Marx’s oeuvre with reflective commentary on how Marx’s work can speak to the contemporary conjuncture, this paper offers a synthetic commentary on how leftists, both scholars and activists, should approach the question of the relationship between radical praxis within capitalism and the character of potential postcapitalisms that may emerge. This essay is loosely organised around three crucial questions: (1) What can we learn from Marx’s discussions on the historical transition and the overall radical intellectual project of dialectical materialism that can assist us in understanding the transition from capitalism to a democratic, egalitarian postcapitalism (i.e., socialism/communism), specifically concerning complexity and time? (2) How does contemporary capitalism reproduce itself social-psychologically (i.e., ideologically) and what are the implications of that for a postcapitalist transformation? (3) What is/are the role(s) of revolutionaries in dealing with the first two questions?